Isolation and identification of tomato bacterial spot pathogen in Ningxia and screening of identification methods for disease resistance - LI Xiaohong; WANG Xiaomin; DENG Wenxia; WANG Kaibin; GUO Meng; CHENG Guoxin (浙江大学学报. 农业与生命科学版)
In order to identify the pathogens causing tomato bacterial spot disease in Ningxia, tomato leaves infected with bacterial spot disease from Zhongwei and Wuzhong cities of Ningxia were used as the materials, and the strains were isolated using the conventional tissue isolation method, and their morphology, molecular biology and pathogenicity were identified. The four-factor and three-level orthogonal design of experiment [L9(34)] was conducted to screen the indoor resistance identification method at the seedling stage. The results showed that the colony morphologies of strain 1 isolated from Zhongwei City and strain 2 isolated from Wuzhong City were all milky white, full edge, opaque, smooth surface, producing green fluorescence, rod-shaped cells, and Gram staining was negative. The 16S rDNA sequences of both strain 1 and strain 2 were 99.93% similar to that of Pseudomonas syringae pv. tomato pathogenic variant KT783475.1. After reinoculation, brown lesions with yellow halos were presented on the leaves of the tomato, which was consistent with the natural symptoms. So, it was confirmed that the pathogen causing tomato bacterial spot disease in Ningxia was P. syringae pv. tomato. Under the treatment combination of inoculating seedlings at the four-leaf stage, the bacterial suspension concentration of 1.00×107 CFU/mL, with stem inoculation method and 96 h moisture, the disease index was 72.22%, which was significantly higher than that in other treatments, and thus it was considered to be the best indoor resistance identification method at the seedling stage for tomato bacterial spot disease. The above results will provide a theoretical basis for the prevention and control of tomato bacterial spot disease and resistance breeding in Ningxia.